REALISASI PERDA NO. 1 TAHUN 2014 TENTANG RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH KABUPATEN POLEWALI MANDAR PERSPEKTIF SIYASAH SYAR’IYYAH - Mundzir, Ibnu; Larissa, Dea (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The purpose of this study was to determine the realization of PERDA No. 1 of 2014 concerning the Regional Medium-Term Development Plan of Polewali Mandar Regency with a siyasa syar'iyyah perspective. This research is a field research with a juridical and syar'i approach. The regional medium-term development program in Polewali Mandar Regency from 2014 to 2019 has been carried out in accordance with the mandate of PERDA No. 1 of 2014 concerning the RPJMD for Polewali Mandar district. Although the implementation of this five-year development has been carried out, in some developments there are still many things that need to be reviewed, because there are still developments that are not in accordance with the wishes and needs of the community and the development that has been carried out touches the main parts of people's lives that have not been realized evenly in all areas. region.